Fundamentos para una iconología audiovisual (Communication & Society, 1988)
FOUNDATIONS FOR AN AUDIOVISUAL ICONOLOGY: Films and television programs are today privileged media which publicly institutionalize the concepts and appraisals of human individuals and their lives within society. In this work, the approach is that of probing the feasibility of their study from a symbolic perspective which updates the allegorical criteria of classical Iconology which tends to matters of this nature. In order to carry out this task it is convenient to maintain two open perspectives: a theoretical approach which is oriented towards the aesthetics of reception, and another approach which bears upon creativity within the production of statements in movies and television. From this dual perspective Iconology presents itself as an Epistemology of the audiovisual culture.